Given \( x>0 \) and \( y>0 \), select the expression that is equivalent to \[ \sqrt{16 x^{7} y^{11}} \]
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To simplify the expression \( \sqrt{16 x^{7} y^{11}} \), we can break it down into its individual components. 1. Start with the square root of the constant and each variable separately. Since \( 16 \) is a perfect square, we have: \[ \sqrt{16} = 4 \] 2. For the variable \( x^{7} \): \[ \sqrt{x^{7}} = \sqrt{x^{6} \cdot x} = \sqrt{x^{6}} \cdot \sqrt{x} = x^{3} \sqrt{x} \] 3. For the variable \( y^{11} \): \[ \sqrt{y^{11}} = \sqrt{y^{10} \cdot y} = \sqrt{y^{10}} \cdot \sqrt{y} = y^{5} \sqrt{y} \] Putting it all together, we have: \[ \sqrt{16 x^{7} y^{11}} = 4 \cdot x^{3} \sqrt{x} \cdot y^{5} \sqrt{y} \] Thus, the expression simplifies to: \[ 4 x^{3} y^{5} \sqrt{xy} \] So, the final answer is: \[ \boxed{4 x^{3} y^{5} \sqrt{xy}} \]